Letramento estatístico na educação básica: o uso de tecnologias digitais em pesquisas de opinião - Felipe Júnio de Souza Oliveira (2019)
This research aimed to investigate and analyze the use of digital technologies, their contributions and limitations, in opinion survey based on the approach of the program Nossa Escola Pesquisa Sua Opinião (Nepso) for a learning in Statistics of 8th year fundamental school students. For this, an educational project of opinion survey was constructed and developed with 16 students of the Pedagogical Center of the Federal University of Minas Gerais, Brazil. This project consisted of the basis for, through participant observation (FIORENTINI; LORENZATO, 2006), to record audio, video and field diary of the proposed activities in eight planned meetings with the active participation of the students in the choice of theme, approaches and issues of interest. As the Nepso program approach became structuring for research, we did not ignore the other discussions that could be made and identified that they were part of the same corpus we call the "Nepso process". In this sense, we opted to analyze our data in a processual way, according to the eight stages of Nepso, describing and interpreting them, qualitatively, aiming to reach our objectives and discuss the following analytical aspects: contributions and limitations of digital technologies in the educational project of opinion survey; development of skills and abilities related to the Nepso based learning project; and skills and aspects of statistical literacy according to the model proposed by Gal (2002). When researching about entertainment, it was possible to notice that the use of Whatsapp, Facebook and Excel provided an optimization of pedagogical time and classroom space, as well as interactive and learning possibilities in the field of Statistical Education. In addition, the development of skills and abilities related to Nepso and the mobilization of the cognitive and affective components of the statistical literacy of Gal (2002) were observed. From the perspective that we have been able to broaden the Nepso discussions on the survey, data collection and processing with the use of digital technologies for statistical literacy, we have developed a support material with discussions aimed at Mathematics teachers wishing to work in this direction with opinion survey online. As a pedagogical implication, we consider that Nepso is also an important didactic investment for Statistical Education and that digital technologies must be present in more of its stages.